2019
DOI: 10.18632/oncotarget.26933
|View full text |Cite
|
Sign up to set email alerts
|

Expression dynamics of Mage family genes during self-renewal and differentiation of mouse pluripotent stem and teratocarcinoma cells

Abstract: The biological roles of cancer-testis antigens of the Melanoma antigen (Mage) family in mammalian development, stem cell differentiation and carcinogenesis are largely unknown. In order to understand the involvement of the Mage family genes in maintenance of normal and cancer stem cells, the expression patterns of Mage-a, Mage-b, Mage-d, Mage-e, Mage-h and Mage-l gene subfamilies were analyzed during the self-renewal and differentiation of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Over the past decades, the MAGE protein family, which is a highly conserved group of proteins that share a common MAGE homology domain, has led to numerous insights that MAGEs were involved not only in stem cell differentiation and tumorigenesis progression, but also in invasion and metastasis. 26,27 MAGE-A11, the unique steroid hormone receptor transcriptional coregulator among the type I MAGEs, is known to be involved in the transcriptional activity of androgen receptor (AR) by binding with p160 in prostate cancer. [28][29][30] Furthermore, MAGE-A11, as a transcriptional activator of E2F1 and androgen receptor, interacts with retinoblastoma-related protein p107 and enhances prostate cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, the MAGE protein family, which is a highly conserved group of proteins that share a common MAGE homology domain, has led to numerous insights that MAGEs were involved not only in stem cell differentiation and tumorigenesis progression, but also in invasion and metastasis. 26,27 MAGE-A11, the unique steroid hormone receptor transcriptional coregulator among the type I MAGEs, is known to be involved in the transcriptional activity of androgen receptor (AR) by binding with p160 in prostate cancer. [28][29][30] Furthermore, MAGE-A11, as a transcriptional activator of E2F1 and androgen receptor, interacts with retinoblastoma-related protein p107 and enhances prostate cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, insufficient ATRA action on neurite outgrowth in Magel2-deficient mice could be associated with potential downstream alterations in vesicle trafficking, as well as the corresponding increased lipid droplet accumulation and changes in neuronal morphology observed in the study by Crutcher et al (2019). Interestingly enough, it has been reported that ATRA can stimulate the expression of Mage family genes, including the Magel2 in various cell lines in vitro (Gordeeva et al, 2019), suggesting that Magel2 is downstream of the ATRA pathway. In this study, we observed decreased expression of Limk1 and Tiam1, which are enzymes known to be associated with rearranging of the cytoskeleton (see scheme in Figure 11) and interact with the retinoid receptor function (Ishaq et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…(2019). Interestingly enough, it has been reported that ATRA can stimulate the expression of Mage family genes, including the Magel2 in various cell lines in vitro (Gordeeva et al., 2019), suggesting that Magel2 is downstream of the ATRA pathway. In this study, we observed decreased expression of Limk1 and Tiam1 , which are enzymes known to be associated with rearranging of the cytoskeleton (see scheme in Figure 11) and interact with the retinoid receptor function (Ishaq et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(2019). Interestingly enough, it has been reported that ATRA can stimulate the expression of Mage family genes, including the Magel2 in various cell lines in vitro (Gordeeva, Gordeev & Khaydukov, 2019), suggesting that Magel2 is downstream of the ATRA pathway. In this study, we observed decreased expression of Limk1 and Tiam1, which are enzymes known to be associated with rearranging of the cytoskeleton (see scheme in figure 11) and interact with the retinoid receptor function (Ishaq et al, 2011).…”
Section: Impaired Neurite Outgrowth In Immature Hippocampal Neurons Imentioning
confidence: 99%